TRENDS IN THE UTILIZATION OF AUGMENTED REALITY AS A LEARNING TOOL FOR STUDENTS IN INDONESIAN ELEMENTARY SCHOOLS - Zakiya, Faza; Sularso, Sularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
Learners are currently growing up in the digital era, they will meet digital technology in the family environment and even the community. Schools need to strive for technological updates to facilitate learners. The aim of this study is to analyze scientific articles to gather resources related to the use of Augmented Reality as a learning medium for student. The approach employed in this article is a literature review. The literature review analysis method employed is descriptive systematic review. The criteria for scientific articles used are sourced from international journals with the latest 5 years from 2019-2025. This article analyzes six articles from ScienceDirect. The results of the analysis of 6 scientific articles obtained more developed types of research and development research and literature review than other types of research. The analysis of these journals reveals that the use of Augmented Reality as a learning medium has both positive and negative effects on students and educational institutions. Despite its drawbacks or potentional negative impacts, with proper management, Augmented Reality learning media can serve as an effective solution for elementary school education in Indonesia. This is due to the ability of Augmented Reality to enhance students’ motivation and interest in learning. Future research is encouraged to explore the use of Augmented Reality as a learning medium for elementary school students in Indonesia through qualitative, quantitative, and research and development metodologies.